Formação para o trabalho: cursos superiores de tecnologia - Ramos, Anna Cristina Pascual (2014)
This research approaches the Education for Work, how higher education prepare people for work. The main goals are: to investigate the socioeconomic profile of such students; to observe the inclusion and professional progression of them into the labor market; to compare the results from public institutions and private institutions; to assess the reasons for choosing Technology courses (at higher education levels) and to verify their interest in specialization - after completing the course; to evaluate the contribution of the course for the student's work life; and finally, contribute to increase the pedagogical organization of these courses; also, criticism about this model of higher education are discussed on the study. It is observed an increasing interest on this model of higher education - education for work/ technology courses - in Brazil today. On this study, we have compared such model with others which presents a similar link between education and work. Thus, it is our interest to investigate the expansion of such educational model as well as the increasing enrollments at institutions which offer such courses. The method applied at this research was bibliographical review and data collection - regarding perspectives of course's coordinators and students (about the courses) from Universidade de Santo Amaro (private) - UNISA and Centro de Educação Tecnológica Paula Souza (public) CEETEPS. Also, the research was submitted to the Ethics in Research Committee from Pontifícia Universidade Católica de São Paulo PUCSP and Universidade de Santo Amaro UNISA (both on metropolitan area of São Paulo city). Moreover, the study have shown that, collected data express, and are equivalent, to the data collected by the government about higher education in Brazil; also, we shall highlight that we have accomplished all researches' goals; showing that has no significant difference between students' profile from private and public institutions on the topics assessed by this research